(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Spirit of work is a feeling of being serious in doing work in order to achieve the best results. The purpose of this study was to determine how transformational leadership influences the non-physical work environment and Spirit of work. The research was conducted at PT. Kembar Putra Makmur Mengwi Badung. The number of samples taken were 44 respondents. The research instrument test uses validity and reliability tests. The data analysis technique is path analysis and Sobel test. The test results show that transformational leadership has a positive and significant effect on Spirit of work at PT. Kembar Putra Makmur Mengwi Badung. Transformational leadership has a positive and significant effect on the non-physical work environment at PT. Kembar Putra Makmur Mengwi Badung. The non-physical work environment has a positive and significant effect on Spirit of work at PT. Kembar Putra Makmur Mengwi Badung. The non-physical work environment is able to mediate the influence of transformational leadership on Spirit of work at PT. Kembar Putra Makmur Mengwi Badung. It is hoped that this research will lead to more frequent teaching or sharing of experiences so that employees have better insight. The company should pay attention to how leaders should establish better communication with their employees.